IMPROVING STUDENT’S VOCABULARY MASTERY THROUGH ENGLISH SONG IN SEVENTH GRADE JUNIOR HIGH SCHOOL - Zurriatun, Siti Mardiah; Rosyidi, Ahmad Zuhri; Yulandari, Evi Safitri (JURNAL ASIMILASI PENDIDIKAN, 2024)
The purpose of this research is to improve students' vocabulary mastery through English songs. This research was Classroom Action Research with conducted in two cycles, each consisting of planning, action, observation, and reflection. Data is collected through qualitative and quantitative data. Qualitative data obtained by interviews and observation results. Then, quantitative data were obtained from the students' vocabulary scores from the pre-test, post-test. Based on the results of this study, it showed that there was progress in students' vocabulary mastery, as seen from the average pretest score of 66.07, the average posttest 1 score was 72.14, and the average posttest score. cycle 2 is 78.93. In addition, there were 5 students (18%) who passed the Standard of minimum completeness of mastery learning on the pretest. Whereas in cycle 1 there were 15 students (54%) who passed Standard of minimum completeness, and it was obtained in the post test cycle 2 that there were 24 students (86%) who passed. It means that, the Standard of minimum completeness of mastery learning was achieved. Then, the results show an increase and a positive response in the learning process of teaching vocabulary through English songs. Furthermore, the results of observations and interviews show that students are motivated in the teaching and learning process when using this English song.